2015
DOI: 10.1002/app.42012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasticizer with different functional groups on thermoplastic starch

Abstract: Retrogradation of amorphous thermoplastic starch (TPS) films obtained by compression molding of spray dried modified potato starch was investigated. The aim was to investigate the influence of plasticizers with similar molecular weight but different functionality, i.e., isoleucine, asparagine and malic acid, on the properties of plasticized powder and TPS films. Combinations of malic acid with glycerol, urea, and maltodextrin were also evaluated. Except for isoleucine formulated starch, all samples were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 47 publications
9
45
0
Order By: Relevance
“…Samples were compressed at 25 bar for 5 min. The molding temperature for all samples was 140°C [5,7].…”
Section: Preparation Of Tps-filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were compressed at 25 bar for 5 min. The molding temperature for all samples was 140°C [5,7].…”
Section: Preparation Of Tps-filmsmentioning
confidence: 99%
“…Malic acid was also found to inhibit the retrogradation of mixed formulations containing the acid and urea, glycerol or maltodextrin. This study again showed that reduced retrogradation leads to high moisture absorption and high strain at break with loss of tensile strengths [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most used starch plasticizers are water and glycerol, but other compounds like polyols, e.g. sorbitol, mannitol, xylitol (Mathew & Dufresne, 2002;Talja, Helén, Roos & Joupilla, 2007), amines: urea (Lourdin, Coignard, Bizot & Colonna, 1997;Wang, Cheng & Zhu, 2014, ethanolamine (Schmitt et al, 2015) triethanolamine (Jost & Stramm, 2016), carboxylic acids or their salts (Lourdin et al, 1997;Niazi, Zijlstra & Broekhuis, 2015), sugars or their mixtures with other plasticizers (Teixeira, Da Róz, Carvahlo & Curvelo, 2007) and its derivatives like isosorbide (Battegazzore, Bocchini, Nicola, Martini & Frache, 2015) glycol/alginate mixtures (López et al, 2015) and ionic liquids (Wilpiszewska & Spychaj, 2012) can be applied as plasticizers.…”
Section: Introductionmentioning
confidence: 98%
“…Carboxylic acids like citric or malic acid are mainly non-toxic and can be obtained from natural origin. They can act not only as crosslinking agents but also as plasticizers (Niazi et al, 2015). Carboxylic acids act in a dual way, they crosslink starch materials by forming ester bonds between their carboxyl groups and hydroxyl groups onto polymeric chains but may also cause chain scission by acidic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%